Resolved Convection in Hydrogen-rich Atmospheres - Jacob T. Seeley; Robin D. Wordsworth (The Planetary Science Journal)
In hydrogen-rich atmospheres with low mean molecular weight (MMW), an air parcel containing a higher-molecular-weight condensible can be negatively buoyant even if its temperature is higher than the surrounding environment. This should fundamentally alter the dynamics of moist convection, but the low-MMW regime has previously been explored primarily via 1D theories that cannot capture the complexity of moist turbulence. Here, we use a 3D cloud-resolving model to simulate moist convection in atmospheres with a wide range of background MMWs and confirm that a humidity threshold for buoyancy reversal first derived by T. Guillot coincides with an abrupt change in tropospheric structure. Crossing the “Guillot threshold” in near-surface humidity causes the dry (subcloud) boundary layer to collapse and be replaced by a very cloudy layer with a temperature lapse rate that exceeds the dry adiabatic rate. Simulations with reduced surface moisture availability in the lower atmosphere feature a deeper dry subcloud layer, which allows the superadiabatic cloud layer to remain aloft. Our simulations support a potentially observable systematic trend toward increased cloudiness for atmospheres with near-surface moisture concentrations above the Guillot threshold. This should apply to H _2 O and potentially to other condensible species on hotter worlds. We also find evidence for episodic convective activity and associated variability in cloud cover in some of our low-MMW simulations, which should be investigated further with global-scale simulations.